Dietary risk assessment methodology: how to deal with changes through life. Issue 5 (3rd May 2020) - Pruvost-Couvreur, Manon; Le Bizec, Bruno; Béchaux, Camille; Rivière, Gilles
ABSTRACT: Chemicals are present in food and numerous methods have been developed to assess dietary risk associated with these substances, but mainly by studying short periods of exposure. Usually, consumption data used to assess the risk are collected over a short period-of-time. The aim of this paper was to compile existing methods to assess dietary risk and identify their limitations in terms of lifetime risk assessment. To this end, we reviewed the different methods currently used at each step of risk assessment (i.e. methods to collect consumption data, to compute dietary exposures, and then to interpret these exposures in terms of risk for the consumer). Numerous methodologies exist to collect consumption data, contamination data collection, as well as for data treatment and interpretation. These methods consider different hypotheses and therefore lead to numerous uncertainties and discrepancies in the estimation of the exposure. Moreover, changes in eating habits through life, evolutions of food contamination, as well as health risk induced by fluctuating exposures, are rarely studied. A scientific consensus on the current risk assessment approaches is needed between national regulatory authorities. Moreover, additional research activities appear needed to take the evolution of consumption and contamination through time into account and to be able to assess the dietary health risk over the entire life.